Risk Factors for Failure of Hard Palate Mucoperiosteal Flap Repair of Acquired Oronasal Communication in Dogs: A Pilot Study - Taney, Kendall; Smith, Mark M.; Cummings, Nathan P.; Lozano, Alicia J. (Frontiers in Veterinary Science, 2021)
The objective of this retrospective pilot study was to describe potential risk factors for failure of hard palate mucoperiosteal flaps (HPF) transposed for closure of oronasal communication. Dogs (n=28) with acquired oronasal communication defects were included in the study population. Functional success of an HPF was determined by visual inspection at the last examination and lack of clinical signs. Risk factors for HPF failure including age, sex, body weight, presence of neoplasia at the time of surgery, presence of neoplasia after surgery due to incomplete or narrow margins, use of CO2 laser, previous surgeries in the same location, HPF blood supply, size of the HPF as a percentage of the total area of the hard palate mucoperiosteum, and distance traveled by the apex of the HPF were evaluated using descriptive statistics and unadjusted logistic regression modeling. Seven out of 28 (25%) hard palate flap procedures resulted in persistent oronasal communication and were considered failures. Presence of neoplasia at the time of surgery (86% vs. 57%, OR = 4.50, 80% CI = 1.01, 20.06), HPF area (Median: 0.49 vs. 0.41, OR = 84.40, 80% CI = 1.66, 4298) and apex travel distance (Median: 2.06 vs. 0.67, OR = 5.15, 80% CI = 2.14, 12.38) were associated with flap failure. Within this sample, the presence of neoplasia at the time of initial surgery, increasing the area of the HPF, and distance traveled by the HPF apex were associated with a greater odds of HPF failure. Further studies with larger sample sizes are needed to confirm repeatability of these results. HPFs remain a viable surgical option for closure of oronasal communication. Careful surgical planning, strict adherence to surgical principles, and awareness of anatomical limitations can increase the likelihood of success.